THE RELATIONSHIP BETWEEN SOCIAL SUPPORT AND SUBJECTIVE WELL-BEING IN STUDENTS OF THE FACULTY OF PSYCHOLOGY AND EDUCATION, UNIVERSITY OF MUHAMMADIYAH SIDOARJO - Nuranik, Nuranik; Ansyah, Eko Hardi (Journal of Social Science, 2024)
Subjective well-being is a cognitive and affective evaluation of life. The number of students who are stressed with their academic activities, experiencing anxiety and depression indicates a subjective well-being problem. The study aims to determine the relationship between social support and subjective well-being in students of the Faculty of Psychology and Education, Muhammadiyah Sidoarjo University. This type of research is quantitative using a correlational approach. The study population was students of the Faculty of Psychology and Education, University of Muhammadiyah Sidoarjo, totaling 2,000. The sample of this study amounted to 301 based on the Isaac & Michael table with an error rate of 5%. Sampling using purposive sampling technique where sampling is based on the criteria of active students of the Faculty of Psychology and Education in 2023/2024. The research data collection technique used a scale of social support and subjective well-being. The data analysis technique uses Spearmans Rho's product moment correlation with the help of SPSS 26.0 for windows. the result of the correlation coefficient is 0.505 with a smaller significance value of 0.000 <0.05. These results indicate a significant positive relationship between social support and subjective well-being in students of the Faculty of Psychological and Educational Sciences, Muhammadiyah Sidoarjo University. The higher the level of student social support, the higher the level of subjective well-being felt by students and vice versa